2016
DOI: 10.1139/cjps-2016-0048
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for root vigor and days to flowering in Brassica napus L.

Abstract: A segregating F 2 population was developed from a winter and spring type cross to identify quantitative trait loci (QTL) controlling root vigor and days to flowering in canola (Brassica napus). About 3090 polymorphic SNPs derived from genotyping by sequencing were used to develop a linkage map. A final linkage map was constructed with 658 SNPs at LOD 4. One QTL, NRV (Napus Root Vigor) was identified on chromosome A01 (24.7 Mbp) for root vigor explaining 16.3% of the phenotypic variation. GBF Interacting Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 76 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…ArifUzZaman et al. () identify one QTL for root vigour explaining 16% of the phenotypic variation on chromosome A1 (24.7 Mbp).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ArifUzZaman et al. () identify one QTL for root vigour explaining 16% of the phenotypic variation on chromosome A1 (24.7 Mbp).…”
Section: Discussionmentioning
confidence: 99%
“…() reported a total of 131 QTLs for root architectural traits in rapeseed under contrasting P application. A QTL mapping for napus root vigour was identified on chromosome A01 (24.7 Mbp) explaining 16.3% of the phenotypic variation (Arifuzzaman, Mamidi, McClean, & Rahman, ). Furthermore, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…The allelic frequencies for the two DNA bulks are then estimated. The application of genetic studies to rapeseed root traits relies on a phenotyping procedure, which requires growing plants on agar-based medium (Shi et al, 2012;Kiran et al, 2019;Kupcsik et al, 2021), in hydroponics (Zhang et al, 2016;Wang et al, 2017a) or in soil (Arifuzzaman et al, 2016(Arifuzzaman et al, , 2019Louvieaux et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Rapeseed absorbs between 290 to 373 kg ha −1 of K, with the majority of the K coming from the soil. Some studies in B. napus have focused on root traits, specifically the root development at the seedling stage; root vigor; root development at the mature stage; root growth dynamics; variations in root growth habits of spring, winter, and semi-winter rapeseed; and the significance of root morphology in terms of phosphorus and nitrogen absorption [35][36][37][38][39][40][41][42][43]. So far, few studies have identified genetic pathways or genes associated with the architecture of the root system in B. napus grown in low-potassium environments.…”
Section: Introductionmentioning
confidence: 99%